EXTENDED ANTICOAGULANT THERAPYIN PATIENTS, WHO SURVIVED PULMONARY EMBOLISM - Natalia M. Vorobieva; Elizaveta P. Panchenko («REMEDIUM GROUP» Ltd., 2018)
The review article discusses the options to extend anticoagulant therapy after completing the main anticoagulant therapy course in patients, who survived pulmonary embolism. It presents the results of randomized RE-MEDY and RE-SONATE studies of dabigatran, EINSTEIN-Extension study of rivaroxaban and AMPLIFY-Extension study of apixaban, which evaluated the feasibility, efficacy and safety of extended anticoagulant therapy with direct acting oral anticoagulants compared with placebo or warfarin. The article also provides the results of ASPIRE and WARFASA studies, which evaluated the possibility of using low-dose aspirin vs. Placebo for the extended treatment. The authors reviewed in details the results of einstein choice study, in which they compared the extended therapy with two doses of rivaroxaban (10 or 20 mg once a day) versus low (100 mg/day) doses of aspirin and against each other. The data obtained indicate that both doses of rivaroxaban significantly exceed aspirin in efficacy and reduce the risk of recurrent venous thrombosis by 74 and 66 %, respectively, without significantly increasing the risk of bleeding.